1999
DOI: 10.1118/1.598739
|View full text |Cite
|
Sign up to set email alerts
|

On the statistical nature of mammograms

Abstract: We show that digitized mammograms can be considered as evolving from a simple process. A given image results from passing a random input field through a linear filtering operation, where the filter transfer function has a self-similar characteristic. By estimating the functional form of the filter and solving the corresponding filtering equation, the analysis shows that the input field gray value distribution and spectral content can be approximated with parametric methods. The work gives a simple explanation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 31 publications
5
76
2
Order By: Relevance
“…37,39,47 These results differ from those reported by Bochud et al 48 that are higher compared to the results of this and other published studies. This is attributed to the use of constant ring width approach and that the authors used the linear part of the fit to estimate the ␤ value.…”
Section: Ivb Objective Evaluationcontrasting
confidence: 57%
“…37,39,47 These results differ from those reported by Bochud et al 48 that are higher compared to the results of this and other published studies. This is attributed to the use of constant ring width approach and that the authors used the linear part of the fit to estimate the ␤ value.…”
Section: Ivb Objective Evaluationcontrasting
confidence: 57%
“…Images of real anatomy, of course, present a mixture of quantum noise and background anatomical structure. The frequency content of the latter has been described in terms of a 1 / f ␤ characteristic-an approach common in 2D mammography [41][42][43] and recently extended to 3D imaging. 22,[44][45][46] Such anatomical NPS may be added to the quantum NPS in "generalized" forms 47,48 of the NEQ and detectability index, typically diminishing the importance of the low-frequency NEQ and causing a greater contribution to task performance from the high-frequency image characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of anatomical background on detectability is a subject of considerable interest, commonly modeling the background as power-law noise j=f b included as an additive noise term in the "generalized" NEQ. For example, in breast imaging, the power-law characteristic in 2D mammographic images was characterized by Bochud et al, 21 Burgess, 22,23 and others 24 and extended to 3D breast imaging by Metheany et al, 25 Engstrom et al, 26 Glick et al, 27 Gong et al, 28 and Reiser and Nishikawa, 29 showing b differs in 2D projections versus 3D tomosynthesis and CBCT reconstructions. In a fairly general context, Gang et al 30 showed power-law background noise to arise from superposition of self-similar (fractal) structures in 2D and 3D images, derived relations between b in projection, tomosynthesis, and CBCT, and incorporated the result in a generalized detectability index.…”
Section: Introductionmentioning
confidence: 99%